2000
DOI: 10.1177/104365960001100106
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Partnership for Culture Care: Enhancing Health Services for the Arab Community

Abstract: The purpose of this study was to discover perceptions, experiences, and patterns of health care behavior among Arab Americans in an urban Midwestern area of the United States and then to discover perceptions and experiences of health care providers related to culturally competent care. The goal of the study was to generate findings that would provide the basis for implementing system-wide changes to include culturally competent care. A qualitative focus group methodology was used to discover the care patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 6 publications
0
54
0
Order By: Relevance
“…Vicarious shame, which was measured by an item that read, "It is shameful to have people with HIV/ AIDS in Saudi Arabia," was supported by 68.4% of participants. These findings demonstrate that shame, a master emotion for Arabs that guides and colors their perspectives and behaviors (Kulwicki, Miller, & Schim, 2000), influenced Saudi students' reactions to individuals with HIV/AIDS. Saudi students might associate AIDS with shame because they perceive AIDS more as a moral-religious issue than as a health condition.…”
Section: Discussionmentioning
confidence: 98%
“…Vicarious shame, which was measured by an item that read, "It is shameful to have people with HIV/ AIDS in Saudi Arabia," was supported by 68.4% of participants. These findings demonstrate that shame, a master emotion for Arabs that guides and colors their perspectives and behaviors (Kulwicki, Miller, & Schim, 2000), influenced Saudi students' reactions to individuals with HIV/AIDS. Saudi students might associate AIDS with shame because they perceive AIDS more as a moral-religious issue than as a health condition.…”
Section: Discussionmentioning
confidence: 98%
“…There is substantial evidence that culturally competent approaches to care, including language services, staff training, culturally appropriate health promotion, and organizational support, are effective (Taylor, 2005). Kulwicki, Miller, and Schim (2000) advocate for cultural diversity training for health care professionals caring for Arabs to address issues of discrimination, stereotyping, and prejudice. Culturally sensitive care would enhance the health of Emirati women.…”
Section: Discussion/conclusionmentioning
confidence: 98%
“…Even so, Cortis [32] found that nurses had difficulties in linking culture and spirituality to care, in order to meet the needs of minority ethnic patients. The importance of avoiding stereotypical thinking when encountering patients, especially for those who do not share the traditional majority culture, is highlighted by Brämberg [33] and Kulwicki, Miller & Myers Schim [34] . Simply having knowledge of specific cultural beliefs, traditions and practices in and of themselves is far from sufficient for developing essential caring skills [35,36] .…”
Section: Discussionmentioning
confidence: 99%